Cholangiocarcinoma-derived secreted products and growth arrest-specific 2-like 3 enhance migratory and invasive abilities of fibroblasts - Natnicha Paungpan; Kulthida Vaeteewoottacharn; Paweena Dana; Saowaluk Saisomboon; Sittiruk Roytrakul; Wiphawi Hipkaeo; Yada Polsan; Kanlayanee Sawanyawisuth; Sukanya Luang; Worachart Lert-itthiporn; Vor Luvira; Chawalit Pairojkul; et al. (European Journal of Cell Biology, 2025)
Cholangiocarcinoma (CCA) is a highly aggressive cancer with limited treatment options, which highlights the urgent need for alternative therapies. One hallmark of CCA is an increase in cancer-associated fibroblasts (CAFs) accompanied by a desmoplastic reaction and fibrosis. However, the roles of CCA-secreted products in fibroblast recruitment remain unclear. This study aimed to identify the chemotactic factors in CCA-secreted products including conditioned media (CCA-CM) and exosomes that promote fibroblast recruitment. The effects of the CCA-CM and exosomes on fibroblast migration and invasion were assessed. The exosomal protein content was analyzed by tandem mass spectrometry. The role of the selected candidate protein, growth arrest-specific 2-like 3 (GAS2L3), in promoting fibroblast migration was investigated using immortalized fibroblasts and CCA-derived CAFs. These results demonstrated that both CCA-CM and exosomes significantly enhanced fibroblast migration, with GAS2L3 playing a critical role in this process. The involvement of CCA-CM and GAS2L3 in fibroblast recruitment was confirmed in clinical CAFs. To our knowledge, this study provides the first evidence that CCA-derived secreted products and GAS2L3 enhance fibroblast migration. These findings suggest CCA-derived GAS2L3 represents a novel therapeutic target for disrupting the interactions between CCA and CAFs, potentially hindering fibroblast recruitment during CCA treatment.